2006
DOI: 10.1007/s00018-006-6140-5
|View full text |Cite
|
Sign up to set email alerts
|

The intriguing prion disorders

Abstract: Prion diseases are among the most intriguing illnesses. Despite their rare incidence, they have captured enormous attention from the scientific community and general public. One of the most hotly debated issues in these diseases is the nature of the infectious material. In recent years increasing evidence has emerged supporting the protein-only hypothesis of prion transmission. In this model PrPSc (the pathological isoform of the prion protein, PrPC) represents the sole component of the infectious particle. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 109 publications
1
39
0
Order By: Relevance
“…At present, however, although there are clear indications that cholesterol-enriched microdomains (rafts) are essential for the proper folding of nascent PrPc protein, there are divergent findings regarding whether cellular cholesterol depletion or its enrichment would favour the misfolding of PrP. A number of studies have, in fact, shown a decrease of PrPsc generation by lowering the cellular cholesterol content with statins [7,19,20], while other studies produced evidence that cholesterol depletion abolishes PrP-raft association, promotes its accumulation and increases substantially its misfolding [28,29]. In addition, replication of misfolded PrP protein was reported to interfere with the raft composition by displacing raft proteins, such as Cav-1, likely leading to alterations of intracellular cholesterol trafficking and accumulation [30].…”
Section: Discussionmentioning
confidence: 99%
“…At present, however, although there are clear indications that cholesterol-enriched microdomains (rafts) are essential for the proper folding of nascent PrPc protein, there are divergent findings regarding whether cellular cholesterol depletion or its enrichment would favour the misfolding of PrP. A number of studies have, in fact, shown a decrease of PrPsc generation by lowering the cellular cholesterol content with statins [7,19,20], while other studies produced evidence that cholesterol depletion abolishes PrP-raft association, promotes its accumulation and increases substantially its misfolding [28,29]. In addition, replication of misfolded PrP protein was reported to interfere with the raft composition by displacing raft proteins, such as Cav-1, likely leading to alterations of intracellular cholesterol trafficking and accumulation [30].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (1,9,17,32,35) have pointed out the essential role of cellular cholesterol for the proper folding and trafficking of PrPc, indicating that the conversion rate of PrPc into PrPsc may be modulated, at least in part, by cholesterolhomeostatic mechanisms. Conversely, PrPsc replication itself has been reported (34) to interfere with intracellular cholesterol metabolism and trafficking by displacing the cholesterol binding protein caveolin 1 from the membrane, thus suggesting that PrP perturbations may in turn exacerbate preexisting cholesterol alterations.…”
Section: Discussionmentioning
confidence: 99%
“…10 ) and the recombinant mouse prion protein recMoPrP 89-230 (ref. 11 ). We ask whether known chemical aggregators can inhibit amyloid fiber formation, whether known fibrillization inhibitors form colloidal aggregates and whether amyloid inhibition by these molecules is in fact mediated via colloidal aggregation.…”
mentioning
confidence: 99%